Transmedia Storytelling and the Apocalypse - Joyce, Stephen (Springer International Publishing, 2018)
This book confronts the question of why our culture is so fascinated by the apocalypse. It ultimately argues that while many see the post-apocalyptic genre as reflective of contemporary fears, it has actually co-evolved with the transformations in our mediascape to become a perfect vehicle for transmedia storytelling. The post-apocalyptic offers audiences a portal to a fantasy world that is at once strange and familiar, offers a high degree of internal consistency and completeness, and allows for a diversity of stories by different creative teams in the same story world. With case studies of franchises such as The Walking Dead and The Terminator, Transmedia Storytelling and the Apocalypse offers analyses of how shifts in media industries and reception cultures have promoted a new kind of open, world-building narrative across film, television, video games, and print. For transmedia scholars and fans of the genre, this book shows how the end of the world is really just the beginning....